2022
DOI: 10.3389/fonc.2022.913670
|View full text |Cite
|
Sign up to set email alerts
|

CD3D Is an Independent Prognostic Factor and Correlates With Immune Infiltration in Gastric Cancer

Abstract: The protein encoded by CD3D is part of the T-cell receptor/CD3 complex (TCR/CD3 complex) and is involved in T-cell development and signal transduction. Previous studies have shown that CD3D is associated with prognosis and treatment response in breast, colorectal, and liver cancer. However, the expression and clinical significance of CD3D in gastric cancer are not clear. In this study, we collected 488 gastric cancer tissues and 430 paired adjacent tissues to perform tissue microarrays (TMAs). Then, immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
(34 reference statements)
2
9
0
Order By: Relevance
“…The results presented that CD3D expression was associated with the four immune cells, IRF1 and CCL3 expression with the five immune cells, and FN1 only with three immune cells (Figure 4F–V). In addition, DNA methylation of CD3D in breast, bladder, and gastric cancers has been reported 23–25 . Our study also found that CD3D gene expression had the highest correlation with its methylation level in UM.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The results presented that CD3D expression was associated with the four immune cells, IRF1 and CCL3 expression with the five immune cells, and FN1 only with three immune cells (Figure 4F–V). In addition, DNA methylation of CD3D in breast, bladder, and gastric cancers has been reported 23–25 . Our study also found that CD3D gene expression had the highest correlation with its methylation level in UM.…”
Section: Resultssupporting
confidence: 69%
“…Epigenetic regulation is a major factor in driving transcriptional activation of an array of genes that are essential for immunity in cancer, including T cell receptor genes (for instance, CD3D); a high adverse correlation between the promoter CpG methylation and CD3D expression has been detected in renal and thyroid cancers 40 . Previous results showed highly expressed CD3D in gastric cancer tissues compared with paracancerous tissues and positively correlated with immune infiltration in gastric cancer 23 . Furthermore, CD3D has an intensive correlation with CD8 + T cells, and its upregulation can increase T cell immune infiltration in the tumor microenvironment and induce antitumor immunity by activating T lymphocytes in breast carcinoma 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that CD3D may serve as a prognostic maker of colon cancer, gastric cancer and other tumors ( 33 , 34 ); CD3E can be used as a prognostic factor of lung cancer ( 35 ); the expression of CD247 was associated with many cancers, including gastric cancer, head and neck cancer and ovarian cancer ( 36 38 ). Very few studies mentioned that CD3G was related to the initiation of CESC or the other cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a correlation was also observed between ERCC1 expression and HRD, thus suggesting that ERCC1 expression could also reduce the efficacy of chemotherapeutic drugs like cisplatin and carboplatin. T cells play an important role in cancer, CD3 is an important T cells biomarker, and CD3 deficiency of CD3 could lead to severe combined immunodeficiency ( 21 , 22 ). CD206 is an important biomarker of M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%